Marginal contribution of game statistics to probability of winning at different levels of competition in basketball: Evidence from the Euroleague - Özmen, M. U. (International Journal of Sports Science & Coaching, 2016)
In this study, we analyse the marginal contribution of team level game statistics to the probability of winning a basketball game at various competitive levels considering data from 14 seasons of the Euroleague. Different from the existing literature, we directly compute the marginal contribution of producing one more unit of each game statistic than the opponent to the probability of winning. We also differentiate our analysis over three stages of the Euroleague season that exhibit distinct levels of competitiveness. Results suggest sizeable differences in terms of contribution of game statistics across different levels of competition. As better performing teams advance, marginal contributions of game actions, especially defensive rebounding, assists, turnovers and shooting accuracy are considerably greater in absolute terms at more competitive stages. The most striking effect, however, is related to turnovers. While registering one turnover more than the opponent reduces the probability to win by 13% during the regular season (less competitive stage) and by 17% during Top-16 (the second competitive stage), it reduces the probability to win by 41% at the Play-offs stage (more competitive stage). Such a large impact may alter training and coaching strategies.